2022
DOI: 10.3389/fendo.2022.833644
|View full text |Cite
|
Sign up to set email alerts
|

Ketoconazole- and Metyrapone-Induced Reductions on Urinary Steroid Metabolites Alter the Urinary Free Cortisol Immunoassay Reliability in Cushing Syndrome

Abstract: IntroductionTwenty-four-hour urinary free cortisol (24h-UFC) is the most used test for follow-up decision-making in patients with Cushing syndrome (CS) under medical treatment. However, 24h-UFC determinations by immunoassays (IA) are commonly overestimated because of steroid metabolites’ cross-reaction. It is still uncertain how ketoconazole (KTZ)- and metyrapone (MTP)-induced changes on the urinary steroid metabolites can alter the 24h-UFC*IA determinations’ reliability.Methods24h-UFC was analyzed by IA and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Finally, although the urine of the patients treated with steroidogenic inhibitors did not show changes in 11βHSD2 activity, a reduction in CYP3A4 activity was observed. Although the causal effect of each drug on CYP3A4 activity cannot be concluded from this study due to the small number of patients and concomitant medications, the results show that patients treated with steroidogenesis inhibitors may present with significant changes in their excretion of free steroid metabolites, as previously observed in a total steroid urine profile [39]. Although the clinical relevance of monitoring these changes in cortisol metabolism should be further assessed, the results point to a considerable impact on the follow-up of these patients if urine cortisol measurements are performed using immunoassay and support the use of mass spectrometry measurements for a proper and comprehensive evaluation of the effects.…”
Section: Discussionmentioning
confidence: 49%
“…Finally, although the urine of the patients treated with steroidogenic inhibitors did not show changes in 11βHSD2 activity, a reduction in CYP3A4 activity was observed. Although the causal effect of each drug on CYP3A4 activity cannot be concluded from this study due to the small number of patients and concomitant medications, the results show that patients treated with steroidogenesis inhibitors may present with significant changes in their excretion of free steroid metabolites, as previously observed in a total steroid urine profile [39]. Although the clinical relevance of monitoring these changes in cortisol metabolism should be further assessed, the results point to a considerable impact on the follow-up of these patients if urine cortisol measurements are performed using immunoassay and support the use of mass spectrometry measurements for a proper and comprehensive evaluation of the effects.…”
Section: Discussionmentioning
confidence: 49%
“…Furthermore, a recent publication reported that ketoconazole and metyrapone may alter the urinary excretion of steroid metabolites, thereby leading to a high risk of overestimating their biochemical impact [44]. With respect to LNSC a high intra patient variation of almost 50% is has been reported [43].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Nevertheless, repetitive blood sampling over a day may allow for serum cortisol day curves, which provide a robust estimate of the endogenous cortisol secretion capacity over 24 h. 24h-UFC is also widely used in the monitoring of steroidogenesis inhibitors [40], but a high intra-patient coefficient of variation has to be considered [42,43]. Furthermore, a recent publication reported that ketoconazole and metyrapone may alter the urinary excretion of steroid metabolites, thereby leading to a high risk of overestimating their biochemical impact [44]. With respect to LNSC, a high intra-patient variation of almost 50 % has been reported [43].…”
Section: Drug Monitoringmentioning
confidence: 99%
“…Exposure to excess glucocorticoids can result in complications, such as diabetes mellitus and dyslipidaemia. Assessment of the metabolome using ultra-high-performance liquid chromatography-tandem mass spectrometry has been shown to discriminate hypercortisolaemic patient specimens versus eucocortisolaemic [ 144 ]. It is possible that this type of technique, including molecular (see below), may have value in borderline cases where neither clinical nor biochemical findings can confirm or refute the diagnosis of hypercortisolaemia, but it has yet to be used outside a research setting.…”
Section: Other Testsmentioning
confidence: 99%
“…However, these agents result in structurally similar metabolites to cortisol, such as 11-deoxycortisol, which risks over treatment of spurious hypercortisolism or missing hypoadrenalism due to over treatment [ 25 , 26 ]. It is therefore vital to assess cortisol with an assay free from interference in the presence of steroidogenesis inhibition, and the method of choice would be LC-MS/MS methods validated to be free from interference [ 25 , 144 ]. However, protocols involving immunoassay with urine and saliva have been reported [ 149 ].…”
Section: Testing In Medically Treated Cushing Syndromementioning
confidence: 99%